STRATEGI PENINGKATAN KINERJA PEGAWAI MELALUI PERANAN BUDAYA ORGANISASI, MOTIVASI DAN KEPUASAN KERJA PADA BADAN PENGEMBANGAN SDM ESDM DI KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL RI - Edi Sugiono; Meilad Fitriana (Universitas Nasional, 2018)
This research aims to analyze the strategy to improve employee performance through the role of organizational culture, motivation and job satisfaction in Human Resources Development Agency of Ministry of Energy and Mineral Resources of the Republic of Indonesia.That aims will be achieved by test and analyze the influence of organizational culture, motivation and job satisfaction on employee performance in Human Resources Development Agency of Ministry of Energy and Mineral Resources of the Republic of Indonesia. This research used cross sectional data that obtained from questionnaire distribution to respondents. Population that used in thisresearch is all employees of Human Resources Development Agency of Ministry of Energy and Mineral Resources of the Republic of Indonesia that consist of 334 employees. By using Slovin formula, samples that used in this research consist of 182 respondents. Sampling method that used was simple random sampling method. This research used multiple linear regression method. Results of the research showed that organizational culture, motivation and job satisfaction partially has positive and significant influence on employee performance in Human Resources Development Agency of Ministry of Energy and Mineral Resources of the Republic ofIndonesia.